2019
DOI: 10.1039/c9nh00006b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale antiadhesion properties of sophorolipid-coated surfaces against pathogenic bacteria

Abstract: By means of single-cell force nanoscopy we show that sophorolipid biosurfactants feature unusually strong antiadhesion properties against nosocomial pathogens involved in catheter-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Sophorolipids adsorbed onto gold surfaces showed a compelling reduction in the viability of some significant Gram-positive ( Enterococcus faecalis , Staphylococcus epidermidis , Streptococcus pyogenes ) and Gram-negative ( Escherichia coli , Pseudomonas aeruginosa and Salmonella typhymurium ) pathogens, as reported by Valotteau et al [ 24 ]. These reports feed into a potential application of SLs in antiadhesion therapy, which is proposed as an alternative to the use of antibiotics and antifungal drugs for treating biofilm-associated infections [ 25 ]. According to the authors, SLs exhibited strong and versatile antiadhesion properties against two well known nosocomial pathogens, Staphylococcus aureus and Escherichia coli , making these surfactants promising candidates for the design and production of anti-infective biomaterials.…”
Section: Anti-microbial Propertiesmentioning
confidence: 99%
“…Sophorolipids adsorbed onto gold surfaces showed a compelling reduction in the viability of some significant Gram-positive ( Enterococcus faecalis , Staphylococcus epidermidis , Streptococcus pyogenes ) and Gram-negative ( Escherichia coli , Pseudomonas aeruginosa and Salmonella typhymurium ) pathogens, as reported by Valotteau et al [ 24 ]. These reports feed into a potential application of SLs in antiadhesion therapy, which is proposed as an alternative to the use of antibiotics and antifungal drugs for treating biofilm-associated infections [ 25 ]. According to the authors, SLs exhibited strong and versatile antiadhesion properties against two well known nosocomial pathogens, Staphylococcus aureus and Escherichia coli , making these surfactants promising candidates for the design and production of anti-infective biomaterials.…”
Section: Anti-microbial Propertiesmentioning
confidence: 99%
“…Bacterial adhesion is on average 15% lower on the glycosylated surfaces than on the negative control (Figure 3, red/green bars, left scale), confirming, for longer time scales (> 1 h), the antiadhesive effects attested at the nanoscale by single cell force microscopy. 24 Bacterial cultivability after contact with the substrates (Figure 3, dashed bars, right scale) matches bacterial adhesion for negative controls (Au, cys) and for SL0 and CL samples, indicating that no biocidal effect can be observed for the latter compounds. On the contrary, cultivability is systematically lower than adhesion for GL, SL, SLa, SLt and CLh, suggesting a biocidal effect for these compounds.…”
Section: Biocidal Properties Of Glycosylated Surfacesmentioning
confidence: 75%
“…17,23 The anti-adhesive properties of biosurfactants against pathogenic organisms like E. faecalis, S. mutans or E. coli are particularly interesting, 16 although the general protocol to study anti-adhesion and anti-biofilm properties of biosurfactants only consider a surface dispersion of the compound, this making it particularly vulnerable to washing. To address this issue, sophorolipids were immobilized in surfaces and they have shown a short-term antiadhesive effect (within the first seconds of contact), 24 probably due to repulsive short-distance hydration forces, but also a long-term (> 1h) biocidal effect. These antimicrobial effects are characterized by lysis of both Gram-positive and Gramnegative bacterial cells and decreased bacterial growth capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Insertion of cationic nanoclusters in such brushes also enhanced the removal of S. aureus (24). Two studies identified the antiadhesive properties of negatively charged polymer brushes against E. coli (25) and that of sophorolipid biosurfactants against both E. coli and S. aureus (26). AFM also demonstrated how the herbicide 2,4dichlorophenoxyacetic acid, which induced remodeling of the cell wall of Rhizobium leguminosarum, led to alterations in its surface hydrophobicity (27).…”
Section: Cell Adhesion Forcesmentioning
confidence: 99%